Xin shu shan jian xia = Zu warriors from the Magic Mountain [videorecording (Blu-Ray)] - Yuan, Biao; Mang, Hoi; Situ, Zhuohan; Cheung, Adam, 1947-; Lau, Damian; Ha, Kwong-Li; Lee, Moon, 1965-; Lin, Qingxia; Hung, Samo, 1952-; Chu, Norman, 1955-; Guan Sheng You (Fortune Star Media Limited, 2010)
In the mountains of Zu, an army deserter and his new master teacher must join forces with a devil chaser and his pupil as well as Master Chang Mei to find the Dual Swords and destroy the Blood Devil.